Effects of volatile anesthetics on carotid body response to hypoxia in animals. - Pandit, J; O'Gallagher, K (2008)
This study was a systematic review of the anesthetic effect on carotid body response to hypoxia. We undertook a systematic literature search (electronic plus manual) for full-paper articles in English that used methodologies enabling any anesthetic effect to be located to the carotid body. We found just 7 articles that met our inclusion criteria, incorporating 16 separate studies. Anesthetic (mean dose +/- SD 0.70 +/- 0.33 MAC) significantly depressed carotid body response by 24% (p = 0.041). There were no differences between individual agents (halothane, enflurane, isoflurane) and no influence of the use of neuromuscular blockade or of species (although the data were sufficiently sparse to interpret such sub-group analysis with caution).